2011
DOI: 10.1039/c1cc14627k
|View full text |Cite
|
Sign up to set email alerts
|

Dual colored mesoporous silica nanoparticles with pH activable rhodamine-lactam for ratiometric sensing of lysosomal acidity

Abstract: Alteration of lysosome acidity has been implicated in many biological events ranging from apoptosis to cancer metastasis, etc. Mesoporous silica nanoparticles doped with acid activable rhodamine-lactam and fluorescein isothiocyanate (FITC) were developed for ratiometric sensing of lysosomal pH changes in live cells with flow cytometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 30 publications
0
84
2
Order By: Relevance
“…[14] There have been some reports on the internalization of ratiometric fluorescence pH nanosensors by cells, [15] with localization of the nanoprobes in the cytoplasm [16] or within acidic organelles. [17] Other studies have reported measurements of a change in intracellular pH values using dual ratiometric fluorescence nanoprobes. [18] Recently, a ratiometric polymeric nanoprobe composed of three fluorophores has been reported for intracellular pH measurements.…”
mentioning
confidence: 99%
“…[14] There have been some reports on the internalization of ratiometric fluorescence pH nanosensors by cells, [15] with localization of the nanoprobes in the cytoplasm [16] or within acidic organelles. [17] Other studies have reported measurements of a change in intracellular pH values using dual ratiometric fluorescence nanoprobes. [18] Recently, a ratiometric polymeric nanoprobe composed of three fluorophores has been reported for intracellular pH measurements.…”
mentioning
confidence: 99%
“…As expected, the reports are mostly from MCM-41 MSP and there are only few other materials such as HMM [85] and KIT-6 [111]. Almost all the reports are responsive to pH [111][112][113][114][115][116][117][118], light [85] or redox reactions [119,120], while cancer therapy continues to be the major concern. Different targeting molecules may be used such as folic acid (FA) [5,88,116], guanidine [111] or DNA [120].…”
Section: Macromolecular Layersmentioning
confidence: 89%
“…Recently, some groups [45,46] reported that some of the luminance of CuNCs came from aggregation induced emission (AIE). In order to deeply understand the mechanism of the luminescence of CEW@CuNCs, particle size distribution of the CuNCs in BR buffer with different pH (6,8,10,12) was investigated. As a result of this experiment, it almost had no significant change about the particle size of the CEW@CuNCs, which implied that the aggregation-induced emission was not the reason for the fluorescence increasing of the CuNCs at high pH values.…”
Section: Ph Sensor Of the Cew@cuncsmentioning
confidence: 99%
“…Up to now, fluorescent pH probes have been applied to numerous fields such as analytical application [6], biosensors [7,8] and bio-imaging [9]. Among these fluorescent pH sensors, they can be roughly divided into three categories: organic dye [10,11], semiconductor quantum dots (QDs) [12,13] and metal nano-materials [14,15]. However, most of the organic matter and QDs have toxicity, which limited its application range.…”
Section: Introductionmentioning
confidence: 99%